Adding drama to an EFL class to refresh students’ mind & improve students’ English skills - Lia Agustina (Jurnal Linguistik Terapan, 2011)
Comprehending passages, developing vocabularies into dialogues, creating scenes and plays, and its picturing of an approximate real communication provide a dynamic format in which language skills can be introduced and reinforced. The article is a report of the writer’s experience in using of drama in EFL classes. It is aimed at giving an alternative technique in teaching EFL in Indonesian context. It describes (a) the benefits of implementing drama that performing the integrated language skills in EFL classroom b) how to set it up, and c) how to do it. It was proofed that creating and performing a script-based on improvisation can be a highly successful learning experience for ESL students. While it motivates them to generate imaginative and detailed ideas, greatly expand and mobilize their vocabularies, actively practice language skills and attain far greater fluency. It also provides a setting in which they can explore the social values of a different unique characters among students. Participating in this kind of activity strengthens students' confidence in their academic ability, an essential component of successful language acquisition. Finally, it develops cultural and social awareness, an effective and delightful way to personalize a principle or illustrate a correct thought pattern of live that should be known and implemented by the students.